The Relationship Between 21st-century Teacher Skills and Critical Thinking Skills of Classroom Teacher - Kuloğlu, Ayşenur; Karabekmez, Vahdet (BİLGE AKADEMİK YAYINCILIK EĞİTİM BİLİŞİM VE DANIŞMANLIK HİZMETLERİ, 2022)
This study aims to investigate the relationship between 21st- century teacher skills and critical thinking skills in the classroom teachers. The sample of the study consisted of classroom teachers working in a southeastern city in Turkey. A correlational survey model was used in the study. The 21st-century Teacher Skills Use Scale and the Critical Thinking Scale were used for data collection. The results showed that classroom teachers generally agreed with the statements of the 21st-century Teacher Skills Use Scale and the subscales of technopedagogical skills, flexible teaching skills and confirmative skills, while they always agreed with the subscales of administrative skills and confirmative skills. There was no significant difference between participants' use of 21st-century teacher skills in terms of gender and professional experience. Teachers indicated that they agreed with the statements on the Critical Thinking scale and the Assessment, Self-Control, Self-Regulation, and Self-Confidence subscales and fully agreed with the Decision Making subscale. Although there was no significant difference between critical thinking ability and gender, a significant difference was found between teachers' critical thinking ability and their professional experience. In addition, a positive and moderately significant relationship was found between the use of 21st-century teacher competencies and critical thinking skills in all dimensions. The results indicated that the level of 21st-century skills increased as teachers' critical thinking skills increased.21st-century 21st-century 21st-century 21st-century that the levels of 21st-century skills increased as teachers’ critical thinking skill levels increased
Keywords: Other Fields of Education; Alan Eğitimleri